Adsorption of Orange G dye on nano zirconia: Error analysis for achieving the best equilibrium and kinetic modeling - Gusain D.; Upadhyay S.N.; Chandra Sharma Y. (My University, 2025)
Nano zirconia was used for the adsorption of Orange G dye from aqueous solutions. The best fit linear and nonlinear equations for the two adsorption isotherms and kinetic models, namely the Langmuir and Freundlich adsorption isotherms and pseudo-first-order and pseudo-second-order equations, were compared. The sum of the normalized errors and the coefficient of determination were used to determine the best fit model. The results show that nonlinear forms of isotherms and kinetic equations are more suitable for fitting the experimental data. The adsorption of Orange G over nano zirconia follows the Langmuir isotherm and pseudo-second-order kinetic model more closely than other models. © 2014 the Partner Organisations.